FILANTROPI ISLAM (WAKAF DAN SEDEKAH) DALAM TEORI BOUNDED RATIONALITY HERBERT SIMON PADA ERA DIGITAL: STUDI LITERATUR SISTEMATIK - Siti Aisyah Adelina (Al-Hasyimiyah: Jurnal Ekonomi Syariah, 2026)
ABSTRACT This study aims to analyze the mechanisms of Islamic philanthropy (waqf and sadaqah) in the digital age through the lens of Herbert Simon’s theory of bounded rationality. Using a Systematic Literature Review (SLR) method in accordance with the PRISMA protocol, this study synthesizes 40 key articles to map donor behavior amid the information explosion. The findings reveal a significant gap between the potential for monetary waqf (Rp130 trillion) and the actual realization, which had only reached Rp2.23 trillion as of October 2023. Analysis reveals that digital donors tend to apply the principles of satisficing and emotional heuristics in decision-making to mitigate information overload and decision paralysis. The use of fintech platforms with features that minimize cognitive load, such as QRIS, has proven more effective in triggering donations compared to statistical reports. Additionally, the concept of docility reinforces altruistic behavior through the influence of influencers and social proof on social media. The study concludes that optimizing Islamic philanthropy requires the integration of transparent institutional governance, appropriate choice architecture, and improved Islamic financial literacy to bridge the gap between human cognitive limitations and the potential of digital technology. Keywords: Islamic Philanthropy, Theory of Bounded Rationality, Herbert Simon, Digital Age ABSTRAK Penelitian ini bertujuan menganalisis mekanisme filantropi Islam (Wakaf dan Sedekah) di era digital melalui bingkai teori Bounded Rationality Herbert Simon. Menggunakan metode Systematic Literature Review (SLR) dengan protokol PRISMA, studi ini menyintesis 40 artikel utama untuk memetakan perilaku donor di tengah ledakan informasi. Temuan menunjukkan adanya kesenjangan lebar antara potensi wakaf uang (Rp130 triliun) dengan realisasi yang baru mencapai Rp2,23 triliun per Oktober 2023. Analisis mengungkapkan bahwa donor digital cenderung menerapkan prinsip satisficing dan heuristik emosional dalam pengambilan keputusan guna memitigasi information overload dan decision paralysis. Penggunaan platform fintech dengan fitur yang meminimalkan beban kognitif, seperti QRIS, terbukti lebih efektif memicu donasi dibandingkan laporan statistik. Selain itu, konsep docility memperkuat perilaku altruistik melalui pengaruh influencer dan bukti sosial di media sosial. Penelitian menyimpulkan bahwa optimalisasi filantropi Islam memerlukan integrasi tata kelola lembaga yang transparan, arsitektur pilihan yang tepat, serta peningkatan literasi keuangan syariah untuk menjembatani keterbatasan kognitif manusia dengan potensi teknologi digital. Kata Kunci: Filantropi Islam, Teori Bounded Rationality, Herbert Simon, Era Digital